Influence of Dayak Onion Extract Concentration (Eleutherine palmi folia (L.) Merr) and Length Storage on Weight Decrease, Haugh Unit, and Albumen pH of Duck Egg - Aam Gunawan; Zakir, Muhammad Irwan; Dharmawati, Siti; Rasyidi , Muhammad (Indonesian Journal of Agricultural Research, 2019)
The purpose of this study was to study the effect of immersion on dayak onion extract and storage time and the interaction of these two factors on decreasing of egg weight, haugh unit value and albumen pH of duck egg. The study used a completely randomized design of factorial pattern 4 x 4 with 4 replications. The treatment is as follows: The first factor is the concentration of onion dayak extract (A), consisting of: A0 = Eggs storage placed at room temperature; A1 = 10% concentrated of dayak onion extract; A2 = 20% concentrated of dayak onion extract; A3 = 30% concentrated of dayak onion extract; The second factor is the length of storage (B) consists of: B0 = 7 days. B1 = 14 days. B2 = 21 days. And B3 = 28 days. Research data were analyzed using analysis of variance and continued by Tukey Test. The results showed that the concentration of dayak onion extract did not affect the reduction in egg weight, but did affect the haugh unit and albumen pH. Egg weight reduction ranged from 0.92-1.02. Haugh unit and pH of albumen at 10% and 30% concentration of dayak onion extract did not differ, while the 0% concentration differed from all other treatments. Interaction effects between concentration of dayak onion extract and length storage were also significant for egg weight loss, Haugh unit, and pH of albumen. It is recommended that for preserving duck eggs, it is better to use a concentration of 30% onion extract.